الثقافة البصرية ودورها في إنتاج الشكل الدال في أعمال الفنان محمود شبر - الجنابي، فؤاد يعقوب (الجمعية العلمية للدراسات التربوية المستدامة, 2024)
يتناول البحث الحالي الموسوم (الثقافة البصرية ودورها في إنتاج الشكل الدال في أعمال الفنان محمود شبر) فكرة الثقافة البصرية بين النظرية والتطبيق وما أسهم به الفن العراقي المعاصر بهذا الخصوص، وقد تلخصت مشكلة البحث بالتساؤل الاتي: هل تلعب الثقافة البصرية دوراً في إنتاج الشكل الدال في منجزات الفنان محمود شبر؟ فقد تناول الفنان محمود شبر المواضيع التي تحمل مضمون الثقافة البصرية والشكل الدال في مواضيعه ويهدف البحث إلى كشف دور الثقافة البصرية في إنتاج الشكل الدال في أعمال الفنان محمود شبر. ومن أجل تحقيق هدف البحث قام الباحث بتحليل عينة البحث التي تضمنت أربعة أعمال من أعماله الفنية معتمدة على مؤشرات الإطار النظري ثم اختارت الطريقة القصدية من المجتمع البالغ (۸۸) عملاً فنياً وقد ضم البحث أربعة فصول. تناول الفصل الأول الإطار المنهجي للبحث انف الذكر. وتناول الفصل الثاني الإطار النظري والمؤشرات التي أسفر عنها الإطار النظري، إذ جاء المبحث الأول بعنوان (قراءة في مفهومي الثقافة والثقافة البصرية)، وحمل المبحث الثاني عنوان (الشكل الدال بوصفه استطيقي) في حين جاء المبحث الثاني بعنوان (محمود شبر والتشكيل العراقي المعاصر). بينما تناول الفصل الثالث إجراءات البحث من مجتمع وعينة وأداة ومنهج وتحليل نماذج العينة. وانتهى البحث بالفصل الرابع الذي احتوى على النتائج والاستنتاجات والتوصيات والمقترحات. توصل الباحث إلى جملة من النتائج فأهمها: 1- استعار الفنان في أعماله الفنية الشكل من الخزين والثقافة البصرية ومن ثم إعادة عملية البناء من حيث (الإنشاء التصويري). ٢- إن الشكل عنده أخذ حيزا واسعا في نضم التشكيل الثقافي والفلسفي الجمالي التعبيري لا سيما أن بيئتنا ثرية بالأشكال والمفردات المختلفة. كما توصل الباحث إلى عدد من الاستنتاجات فإن أهمها: 1- أن الرسومات الموجودة في بعض الأعمال ممكن أن تعطينا الهدف والغرض من العمل. The current study, entitled "The Visual Culture and its Role in the Production of the Significant Form in the Works of the Artist Mahmood Shubbar", deals with the idea of visual culture between theory and practice and the contribution of contemporary Iraqi artists in this regard. The research problem was summarized in the following question: Does visual culture play a role in the production of the significant form within the achievements of the artist Mahmood Shubbar? The research aims to reveal the role of visual culture in producing the semantic form in the works of the artist Mahmoud Shubar. In order to achieve the goal of the research, the researcher analyzes the research sample, which includes four works of Mahmood Shubbar’s artworks based on the indicators of the theoretical framework and then chooses the intentional method from (88) artworks. The research has consisted of four chapters. The first chapter deals with the methodological framework of the aforementioned research. The second chapter deals with the theoretical framework and indicators resulting from the theoretical framework. Moreover, the first chapter is entitled (Culture and Visual Culture), and the second chapter carries the title (The Significant Form), while the third chapter is entitled (Mahmood Shubbar and the Contemporary Iraqi Artists). Furthermore, the third chapter deals with the procedures of the research, sample, tool, methodology and analysis of sample models. The research ends with the fourth chapter, which contains the findings, conclusions, recommendations and suggestions. The researcher concludes a number of results, the most important of which are: 1. In his artworks, the artist borrows the form from the storage and visual culture and then re-build them in terms of (pictorial creation). 2. The form has taken a wide space in the inclusion of cultural, philosophical, aesthetic and expressive formation, especially since our environment is rich with different forms and vocabulary. The researcher also concludes a number of conclusions, the most important of which are: 1. Some of his paintings can give us the goals and purposes behind that works.
Keywords: الفنون التشكيلية -- الثقافة البصرية -- التعلم البصري -- العراق